Comparative Study of Naive Bayes Data Mining, Decision Tree C4.5 And Fuzzy Decision Tree (ID3) In Analyzing the Financing of Fitness Center Memberships: Case Study PT Fitindo Sehat Sempurna - Wahyu Joko Saputro; Supriadi Panggabean; Faishal Wafiq Zakiy (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2024)
Abstract - The business world is always experiencing rapid changes, so it requires companies to be able to respond to these changes quickly and precisely. PT. Fitindo Sehat Sempurna as a company engaged in fitness services wants to do data mining to predict the smooth financing of its members and strive to increase sustainable sales turnover. One of the classification algorithms that is often used and gets a lot of attention from researchers in predicting problematic financing is Naive Bayes, Decision Tree C4.5 and then tries to compare it with the Fuzzy Decision Tree (ID3). Of all the trials of the three methods, the best results were obtained, namely Naive Bayes with the highest calculation result of accuracy of 85,00% and AUC = 0,960 as the best results. This test uses 80 training data and 20 testing data.Keywords: Financing, Membership, ID3, Fuzzy, Decision Tree, C4.5, Naive Bayes. Abstrak - Dunia bisnis selalu mengalami perubahan yang cepat, sehingga menuntut perusahaan untuk dapat merespon perubahan tersebut dengan cepat dan tepat. PT. Fitindo Sehat Sempurna sebagai perusahaan yang bergerak di bidang jasa kebugaran ingin melakukan data mining untuk memprediksi kelancaran pembiayaan para anggotanya dan berupaya untuk meningkatkan omset penjualan yang berkelanjutan. Salah satu algoritma klasifikasi yang sering digunakan dan mendapat banyak perhatian dari para peneliti dalam memprediksi pembiayaan bermasalah adalah Naive Bayes, Decision Tree C4.5 dan kemudian mencoba membandingkannya dengan Fuzzy Decision Tree (ID3). Dari semua uji coba ketiga metode tersebut, didapatkan hasil terbaik yaitu Naive Bayes dengan hasil perhitungan akurasi tertinggi yaitu 85,00% dan AUC = 0,960 sebagai hasil terbaik. Pengujian ini menggunakan 80 data training dan 20 data testing.Kata kunci: Pembiayaan, Keanggotaan, ID3, Fuzzy, Decision Tree, C4.5, Naive Bayes